2022
DOI: 10.15586/aei.v50i5.665
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical analysis of Mediterranean Dietary pattern on atopic diseases’ prevalence in adolescence: The Greek Global Asthma Network study

Abstract: Introduction: The contribution of dietary patterns in the occurrence of atopic diseases, mainly asthma, allergic rhinits, and eczema is ambiguous. Our study examined the association between the level of adherence to the Mediterranean diet (MedDiet) and the prevalence of atopic diseases in adolescence. Methods: A total of 1934 adolescents (boys: 47.5%, mean age [standard variation]: 12.7[0.6] years) enrolled voluntarily. Participants completed a validated questionnaire on atopic disease status, dietary habits, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Recent scientific studies have shown that an excessive intake of n-6 fatty acids might cause a physiological condition that heightens platelet aggregation and blood clotting. Higher blood viscosity, vasospasm, vasoconstriction, and slower bleeding are all symptoms of this illness [229][230][231]. In contrast, it has been discovered that n-3 fatty acids offer several advantageous qualities, such as anti-inflammatory, antithrombotic, hypolipidemic, and vasodilatory actions.…”
Section: Polyunsaturated Fatty Acidsmentioning
confidence: 99%
“…Recent scientific studies have shown that an excessive intake of n-6 fatty acids might cause a physiological condition that heightens platelet aggregation and blood clotting. Higher blood viscosity, vasospasm, vasoconstriction, and slower bleeding are all symptoms of this illness [229][230][231]. In contrast, it has been discovered that n-3 fatty acids offer several advantageous qualities, such as anti-inflammatory, antithrombotic, hypolipidemic, and vasodilatory actions.…”
Section: Polyunsaturated Fatty Acidsmentioning
confidence: 99%